SUGARCANE FARMERS IN EAST JAVA: INSTITUTIONAL ARRANGEMENT PERSPECTIVE - Baksh, Rukavina; Yustika, Ahmad Erani (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2008)
In 1930’s decade, Indonesia was recognized as one of the great sugarproducing countries in the world. Sugarcane is mostly grown in East JavaProvince. This area contributes about 40 percent to national sugar production.However, the performance of sugar industry in East Java during the last decadehas declined, which is shown in decreasing volume of production and increasingsugar price. This study utilized the analysis of institutional arrangement to identifythe problems. In details, this research empirically compared contract (credit)and non-contract (non-credit) sugarcane farmers. This research found thatinstitutional arrangements between economic actors in sugar industry are notsuitable, especially for sugarcane farmers. In the case of share-yield system, dueto lack of institutional arrangements, sugarcane farmers rarely get any molassesshare from sugar mill. Another, in the credit point of view, cooperative usuallybears on sugarcane farmers the higher interest from legal rules. Lastly, whencooperative gives aid in the form of seed/fertilizer to sugarcane farmers, it is doneintransparently.Keywords: institutional arrangements, contract systems, sugarcane farmers, EastJava, Indonesia